Endoscopic removal of proximally migrated stents using a double‐balloon enteroscope in patients with bowel reconstruction (with video). Issue 1 (7th September 2021) - Oda, Takashi; Matsumoto, Kazuyuki; Ueta, Eijiro; Himei, Hitomi; Ogawa, Taiji; Terasawa, Hiroyuki; Fujii, Yuki; Yamazaki, Tatsuhiro; Horiguchi, Shigeru; Tsutsumi, Koichiro; Kato, Hironari; Okada, Hiroyuki
Abstract: Endoscopic migrated stent removal using a balloon‐assisted enteroscope is technically difficult in patients with bowel reconstruction. We report the treatment outcomes and endoscopic removal methods for migrated stents using a double‐balloon enteroscope (DBE). We retrospectively studied 12 patients with stent migration into the main pancreatic duct (MPD) or bile duct who underwent bowel reconstruction between January 2012 and June 2020. The successful removal rates in the MPD ( n = 3) and the bile duct ( n = 9) were 66.7% (2/3) and 88.9% (8/9), respectively. The removal techniques included the indirect method ( n = 3), the direct method ( n = 4), and a combination of indirect and direct methods ( n = 3). The removal devices included an extraction balloon catheter ( n = 7), basket catheter ( n = 5), biopsy forceps ( n = 3), and snare ( n = 2). Stent removal using a DBE was feasible and useful as the first treatment for patients with bowel reconstruction. The choice of the direct and/or indirect method according to the situation of the migrated stent is important.